2016
DOI: 10.1111/jbi.12876
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical insight into the Aleutian flora inferred from the historical range shifts of the alpine shrub Therorhodion camtschaticum (Pall.) Small (Ericaceae)

Abstract: Aim The Aleutian Islands, one of the southern margins of Beringia, were covered with ice caps during the Last Glacial Maximum (LGM). Although insular refugia for animal species have been hypothesized in this region, phylogeographical studies have never explored the biogeographical history of plant species. We aim to assess the population history of the flora of the Aleutian Islands and its biogeographical relevance to East Asia.Location The Aleutian Islands, Kamchatka, the Japanese Archipelago.Methods We seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…The blue cluster occurs in Beringia and in northern Japan (Figure ), which largely corresponds to the widespread AFLP cluster dominating in Beringia (no Japanese samples were included in the AFLP study of Eidesen et al., ). Recent phylogeographic studies have revealed genetic similarity as well as demographic closeness between northern Japan and Beringia in alpine as well as arctic‐alpine plants (Hata et al., ; Ikeda, Higashi et al., , Ikeda et al., ), suggesting that cold‐adapted species may have spread widely in northern East Asia. Thus, the present distribution of the blue cluster probably reflects an extensive distribution of K .…”
Section: Discussionmentioning
confidence: 99%
“…The blue cluster occurs in Beringia and in northern Japan (Figure ), which largely corresponds to the widespread AFLP cluster dominating in Beringia (no Japanese samples were included in the AFLP study of Eidesen et al., ). Recent phylogeographic studies have revealed genetic similarity as well as demographic closeness between northern Japan and Beringia in alpine as well as arctic‐alpine plants (Hata et al., ; Ikeda, Higashi et al., , Ikeda et al., ), suggesting that cold‐adapted species may have spread widely in northern East Asia. Thus, the present distribution of the blue cluster probably reflects an extensive distribution of K .…”
Section: Discussionmentioning
confidence: 99%
“…Because there is no specific substitution rate in P . cuneifolia , we assumed 5.3–7.8 × 10 –9 substitutions per site per year to scale the divergence time following our previous studies (Hata et al., 2017; Ikeda et al., 2017, 2018) based on spontaneous mutation rates in Arabidopsis thaliana mutation accumulation lines (Ossowski et al., 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Although a recent study inferred that the arctic–alpine plant Kalmia procumbens colonized central Japan from Beringia during the last glacial period (Ikeda et al., 2017), other studies have not addressed whether Japanese lineages of alpine plants were derived from lineages occurring in Beringia or vice versa. Recent phylogeographic studies have revealed that populations of several alpine plants exhibited high genetic similarity and low genetic diversity across extensive ranges in the northern Pacific region including northern Japan (Hata et al., 2017; Ikeda et al., 2014, 2017; Ikeda, Yakubov, Barkalov, & Setoguchi, 2018). These patterns can be explained by recent range expansion across the northern Pacific region from the Kamchatka Peninsula, which is a part of Beringia.…”
Section: Introductionmentioning
confidence: 99%
“…camtschaticum supports this inference in C . lycopodioides (Hata et al., ). Although sequence variation of seven nuclear loci revealed genetic differentiation between T .…”
Section: Introductionmentioning
confidence: 99%